2016
DOI: 10.1002/atr.1447
|View full text |Cite
|
Sign up to set email alerts
|

A multiple correspondence analysis of at‐fault motorcycle‐involved crashes in Alabama

Abstract: According to the U.S. National Highway Traffic Safety Administration, in 2012, more than 4950 motorcyclists were killed in traffic accidents. Compared to passenger car occupants, mile for mile, motorcyclists are more than 26 times more at risk to dying in crashes. Due to the high fatality rate associated with motorcycle crashes, factors contributing to this type of crash must be identified in order to implement effective safety countermeasures. Given that the available datasets are large and complex, identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…MCA has been chosen as the statistical method to analyze data, given the nature of the datasets and the easiness to interpret the results in a graphical way. In the transport sector, MCA is widely used in road safety analysis, to evaluate the main contributing factors causing accidents [56][57][58] and investigating safety perception [59,60]. MCA has also been used to obtain insight into the quality aspects of PT systems: Lombardo et al [61] computed a composite indicator of customer satisfaction based on the key characteristics for assessing transport service quality found in literature; Grison et al [62] analyzed users' experience of PT route choice on the basis of context and users profiles; citizens' satisfaction for PT through a survey has been investigated in a study conducted for the city of Bologna in Italy [63]: MCA showed that punctuality, frequency of service and efficiency of buses were among the main factors that affected the overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…MCA has been chosen as the statistical method to analyze data, given the nature of the datasets and the easiness to interpret the results in a graphical way. In the transport sector, MCA is widely used in road safety analysis, to evaluate the main contributing factors causing accidents [56][57][58] and investigating safety perception [59,60]. MCA has also been used to obtain insight into the quality aspects of PT systems: Lombardo et al [61] computed a composite indicator of customer satisfaction based on the key characteristics for assessing transport service quality found in literature; Grison et al [62] analyzed users' experience of PT route choice on the basis of context and users profiles; citizens' satisfaction for PT through a survey has been investigated in a study conducted for the city of Bologna in Italy [63]: MCA showed that punctuality, frequency of service and efficiency of buses were among the main factors that affected the overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the police-reported crash data are categorical in nature. Few studies have concentrated on MCA, an exploratory multivariate analysis technique used for handling large and complex nominal crash datasets without any predetermined hypotheses (31)(32)(33). Since development in 1970, MCA has been modified several times to faciltate recognition of variable attribute patterns and their interconnections in multidimensional datasets (34).…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, one of the techniques that have proved to be useful in identifying RTC patterns and typologies in several regions of the world is the multiple correspondence analysis (MCA) [14,15]. MCA is a statistical visualization method for picturing the association between the levels of categorical variables (CVs).…”
Section: Introductionmentioning
confidence: 99%
“…In social sciences [16], marketing [17], economy [18], and health sciences [19], MCA has been used to detect individual and event profiles or typologies, alone or in combination with another technic such as hierarchical clustering. Several studies on road safety have highlighted the value of MCA in studying persons and events (accidents) typologies [14,15]. Some of the advantages of MCA that make it suitable for RTA research in low resource settings are the following: 1) it is specifically designed to deal with nominal or ordinal categorical data, the type of information usually collected in community-based surveys; 2) the availability of several low-cost or even free licensed statistical software that allows its application, and 3) the MCA low learning curve.…”
Section: Introductionmentioning
confidence: 99%